The transcription factor PPAR (Peroxisome Proliferator-activated Receptor) alpha is overexpressed and is associated with a favourable prognosis in IDH-wildtype primary glioblastoma. (31st January 2018) - Haynes, Harry; White, Paul; Hares, Kelly; Redondo, Julia; Kemp, Kevin; Singleton, Will; Killick-Cole, Clare; Stevens, Jonathan; Garadi, Krishnakumar; Guglani, Sam; Wilkins, Alistair; Kurian, Kathreena
Abstract: The peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors governing lipid, carbohydrate and amino-acid metabolism. PPARα agonists such as fenofibrate is in current clinical use as a hypolipidaemic agents. We investigated PPARα in a cohort of primary glioblastoma and the expression of PPARα in large-scale glioblastoma data sets. The clinicopathological features and PPARα expression was examined by immunohistochemistry IHC in primary glioblastoma-IDH wild-type (n=100) and semiquantitively scored by 2 independent pathologists. Total RNA was extracted from macro-dissected regions of glioblastoma (n=48; x10 5µm FFPE unstained sections) and control tissue (temporal lobe epilepsy / healthy brain tissue) (n=17; x10 5µm FFPE unstained sections) using the Omega EZNA. Real time quantitative PCR was performed using a Taqman® Fast Gene Expression Mastermix. PPARα protein expression was examined in post-mortem GM and WM control tissue samples (n=4 GM; n=4 WM) and glioblastoma (IDH1-wildtype) patient samples (n=28). PPARα IHC scores were high in 60/100 and low in 40/100 glioblastoma samples. There was no significant association between PPARα IHC score and patient sex, patient age, Karnofsky Performance Score (KPS), tumour location and MGMT promoter methylation status (p>0.05 for all covariates). RT-qPCR showed a 2.03 fold increase in PPARA mRNA expression in the glioblastoma samples compared to controls (p=0.005) PPARα protein expression was found to be significantly overexpressed in glioblastoma compared to control brain tissue (p=0.032). Within the TCGA data set multivariate analyses identified PPARA gene expression as an independent prognostic marker for overall survival (p=0.042). Hierarchical clustering revealed novel, significant associations between high PPARA expression and a putative set of glioblastoma molecular mediators including EMX2, AQP4 and NTRK2. Conclusions: PPARα protein is overexpressed in primary glioblastoma and high PPARAα gene expression functions as an independent prognostic marker in the glioblastoma TCGA data set.